Komparasi Kebijakan Pemerintah Masa Kepemimpinan Jokowi Periode Pertama Dan Kedua Dilihat Dari Teori Utilitarian - Tsurayya Shafa Kamila (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Justice is one of the benchmarks for knowing the character and way of leading a person, one of which is the head of government in terms of leading the country. This research will discuss the justice provided during President Joko Widodo's two terms of office. Then it is implemented into a policy and then the policies are compared, which period fulfills the characteristics of justice and benefits better. Researchers provide limitations regarding the concepts of justice and benefit in legal policy. This research uses a normative method, namely by reading literature in the form of laws and regulations and government policies that have been made during his term of office in the 2019-2024 period. The aim of this research is to determine the fulfillment of the sense of justice and elements of benefit in the policies that were created during the two periods of President Joko Widodo's leadership.